A coarse-grained model for flexible (phospho)proteins: Adsorption and bulk properties. (January 2015) - Henriques, João; Skepö, Marie
Abstract: Protein adsorption is a complex process that it controlled by several different mechanisms, for example: (i) electrostatic interactions between the protein and the surface, and (ii) between adsorbed proteins; (iii) dispersion interactions; (iv) hydration effects; and (v) structural rearrangements of the protein to balance conformational chain entropy with energetics. The aim of this study was to develop a simple model for the adsorption of intrinsically disordered proteins onto surfaces at a mesoscopic level of detail, while retaining protein integrity. Monte Carlo simulations were used in order to study the thermodynamical and structural properties of the flexible phosphoprotein β-casein, in bulk and adsorbed to hydrophilic silica surfaces, in order to evaluate the effect of varying pH, monovalent salt concentration, and degree of serine phosphorylation. Experimental evidence from our previous study, published in this Journal, was used to set up and tune the Hamiltonian of the model. Our simulations show that protein-surface electrostatic interactions are, indeed, not the main driving force behind adsorption under the simulated conditions. Despite its importance, when taken alone, this type of interaction is not enough to promote the adsorption of β-casein at any salt concentration. Adsorption is only possible through the inclusion of a protein-surface short-ranged attractive interaction potential with a minimum interaction strength of 2.25 kB T . This represents the lowest interaction strength required to mimic experimental adsorption results. An equally important finding is that considerable protein net charge fluctuations, due to phosphorylated serine saturation, have a negligible contribution to the free energy of adsorption. Graphical abstract: Highlights: We develop a general coarse-grained model applicable to a wide range of flexible proteins at charged solid surfaces. β-casein adsorption onto negatively charged silica surfaces has been studied as a function of salt and pH. Besides electrostatics, short-ranged interactions between the protein and surface were found to be crucial. Protein-surface electrostatic interactions are, in fact, less important than expected. Similar adsorption free energy profiles are obtained even after 2/3 of the protein net charge has been turned off.